Delayed treatment of severe hepatitis in unrecognized phalloides syndrome - Pereska, Zhanina; Petkovski, Dushan; Simonovska, Natasha; Babulovska, Aleksandra (European Association of Poisons Centres and Clinical Toxicologists (EAPCCT), 2024)
Objective: Delayed or insufficient antidote treatment of patients with mushroom poisoning is a challenge for every toxicologist[1]. We present a case of delayed recognition of severe phalloides syndrome treated with an additional acetylcysteine dose to the standard protocol with favorable outcome. Case report: A middle-aged man was admitted to the Clinic on the 4th day after ingestion of mushrooms he had picked and eaten under the assumption that they were parasol mushrooms (Macrolepiota procera). He had a medical history of diabetes mellitus type 2, coronary artery bypass graft x3 (only aspirin) and hypertension. Profuse gastroenterocollitis developed 16 h after ingestion (over a weekend) and for the first 2 days he was treated at a local medical center for infectious enterocolitis as an outpatient. Laboratory analyzes on the third day showed an increased transaminase activity with a progressive increase the next day, after which he was brought to the clinic. He was alert, blood pressure 100/60 mmHg, an electrocardiogram (ECG) showed sinus rhythm, heart rate 100/min, pain under the ribs in the right upper quadrant, with yellow discoloration of the sclera. Laboratory analysis revealed platelets 129 10i/L, gamma-glutamyl transferase (GGT) 199 U/L (later 608 U/L), alanine aminotransferase (ALT) 8389 U/L, aspartate aminotransferase (AST) 13804 U/l, lactate dehydrogenase (LDH) 7961 U/L, direct bilirubin 104 mmol/L, blood urea nitrogen (BUN) 17.1 mmol/L, creatinine 133.8 mmol/L, prothrombin time (PT) 29.3 s (11–14 s), and D-dimer 8183 ng/mL. Hepatitis viral marker negative. The patient was intensively rehydrated, treated with IV acetylcysteine (200 mg/kg over 4 h, followed by 100 mg/kg over 16 h, with additional 100 mg/kg dose), oral silymarin (100 mg 3 2) and supportive treatment. Abdominal ultrasound presented enlarged liver (not congested) with intensive steatosis. Progressive thrombocytopenia from day 2 of hospitalization was noted with a nadir of 58 10i/L (150–450 10i/L) on the 9th day of poisoning. He received dexamethasone and low molecular weight heparin (LMWH) and PT normalized on the 8th day of poisoning (14.2 s). The patient recovered after 10 days of treatment, with normalized transaminases after 3 months. The mushroom ingested was assumed to be Amanita phalloides, based on the clinical features, laboratory findings and recognition of the ingested mushroom with a look-alike poisonous mushroom from a mushroom atlas by the patient. Conclusion: Data about the consumption of picked mushrooms should be seriously considered when determining the etiology of severe acute gastroenterocollitis. Delayed treatment of phalloides syndrome may worsen the clinical course and increase the potential risk of lethal outcome.